Quantification of a New Antifungal Drug Based on 1,3,4-Thiadiazole by HPLC-ESI/MS: Method Development, Validation and Pharmacokinetic Application - Sipkina, Nadezhda Yur'evna; Sipkin, Denis Igorevich; Yakovlev, Igor Pavlovich (Drug Research, 2021)
The high sensitive HPLC-ESI/MS method for quantitative determination of a new antifungal drug – 2-[(1Z)-1-(3,5-diphenyl-1,3,4-thiadiazol-2(3Н)-ylidene)methyl]-3,5-diphenyl-1,3,4-thiadiazol-3-ium chloride (TDZ) – was developed and fully validated. TDZ was separated from plasma and urine samples by acetonitrile deproteinization and extraction without time-consuming sample preparation. The reversed-phase high-performance liquid chromatography on Kromasil 100–3.5 C8 column of TDZ in isocratic elution mode using 0.03% trifluoroacetic acid : acetonitrile (65:35, v/v) at a flow rate of 0.2 mL min−1 was performed. Determination of TDZ was carried out by a positive electrospray ionization in a selected ion monitoring mode for [M+]=489 m/z. The method of absolute calibration was used for quantification of TDZ in two concentrations ranges: 100–2500 pg mL−1 and 2500–30 000 pg mL−1. The established method showed a good linearity (R=0.999 for both ranges), the limits of determination and quantification were 50 and 100 pg mL−1, respectively. The Intra- and Inter-day precision values were measured by t-Distribution and Fisher′s Exact Test and were in accordance with the regulatory guidance. Low matrix effects and good recovery were found for TDZ. The present method was successfully applied to determine the pharmacokinetic parameters of TDZ by means of intravenous and oral administrations to rats at 5.0 mg kg−1 and 10.0 mg kg−1, respectively.
Keywords: thiadiazoles; fungicides; liquid chromatography; mass-spectrometry; pharmacokinetics